Distribution and Abundance of Actinomycetes in the Rhizosphere Soil of The Hungayono Karst Ecosystem, Gorontalo - Apriliyanti Mohulaingo; Yuliana Retnowati; Abubakar Sidik Katili; Ani M. Hasan; Novri Youla Kandowangko (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Karst ecosystems have unique environmental conditions that can influence the presence of soil microorganisms, including Actinomycetes in the rhizosphere. This study aimed to determine the distribution and abundance of Actinomycetes in the rhizosphere soil of plants in the Hungayono karst ecosystem, Gorontalo. This study employed a quantitative descriptive method with an exploratory approach. Rhizosphere soil samples were collected from several plant species at three observation points: the lower, middle, and upper parts of the karst area. Actinomycetes were isolated using Starch Casein Agar, while their abundance was determined using the Total Plate Count method and expressed in CFU/g of soil. The results showed that actinomycetes were found at all observation points, with abundances ranging from 2 × 103 to 3 × 105 CFU/g. The highest abundances were found in the rhizosphere of Calamus spp., Anthocephalus macrophyllus, and Ficus microcarpa, while the lowest abundances were found in the rhizosphere of Alocasia macrorrhizos. The Actinomycetes isolates obtained exhibited morphological variation based on mycelium color and colony shape. These findings indicate that the distribution and abundance of Actinomycetes in the rhizosphere soil of the Hungayono karst ecosystem vary among plant species and observation sites. The plant rhizosphere in this karst ecosystem functions as a microhabitat that supports the presence of Actinomycetes and is relevant to studies of karst soil microbiology.